2016
DOI: 10.1038/ejcn.2016.103
|View full text |Cite
|
Sign up to set email alerts
|

Early menarche in normal-weight girls and its association with excess weight, abdominal obesity and metabolic changes at the end of sexual maturation

Abstract: These findings suggest that early menarche did not influence weight, abdominal obesity and serum lipids in the final stage of sexual maturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In a five-year longitudinal study with girls in the ideal weight range at the time of menarche, Araújo et al 3 found no statistically significant differences between girls with and without EM in terms of excess weight, abdominal obesity or abnormal serum lipid levels at the end of sexual maturity. Likewise, Must et al 28 conducted a longitudinal study and found that nutritional status in childhood exerted a greater influence on the occurrence of excess weight in adulthood than EM.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In a five-year longitudinal study with girls in the ideal weight range at the time of menarche, Araújo et al 3 found no statistically significant differences between girls with and without EM in terms of excess weight, abdominal obesity or abnormal serum lipid levels at the end of sexual maturity. Likewise, Must et al 28 conducted a longitudinal study and found that nutritional status in childhood exerted a greater influence on the occurrence of excess weight in adulthood than EM.…”
Section: Discussionmentioning
confidence: 97%
“…Depending on the study, EM is defined from 9 to less than 12 years of age 3,4,5 . According to Gaudineau et al 6 , this variability can be explained by the age of menarche found in different populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the various reasons for these inconsistent findings in the studies of the literature, there are different methods to collect (status quo and recall) and report (mean or median values) the AAM data. Moreover, the age limits used to define early menarche vary depending on the research, even extending to include all those below the median age [ 54 ]. Finally, the cross-sectional design generally applied in these studies may have led to additional difficulties in interpreting the phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several studies have reported controversial results on the association between age at menarche and various cardiometabolic risk factors (6,(9)(10)(11). However, these relationships can be significantly affected by many factors such as ethnicity, geographical region, and socioeconomic status (12).…”
Section: Introductionmentioning
confidence: 99%